Association of Afamin Concentration with Type 1 and Type 2 Diabetes Mellitus - Rebwar Jalal Ali; Sardar Nouri Ahmed (Zanco Journal of Pure and Applied Sciences, 2021)
Afamin is a protein in humans that plays a major role in the regulation of glucose metabolism, insulin sensitivity, so it may be related to diabetes mellitus. The aim of this study to evaluate the afamin concentration level in diabetic patients. This study was a case-control study blood samples were collected from 130 patients of Diabetes mellitus (DM) which divided into two groups (65 types1 DM and 65 type 2 DM) from Laila Qasim center for diabetes in Erbil City. In addition90 healthy volunteers used as a control. Serum was separated to determine afamin concentration. The results showed that the level of afamin in type 2 diabetic patients were significantly higher than those of healthy adults (75.09 + 10.09 mg/L), and (65.62 + 7.18 mg/L) respectively, No significant differences in the concentration of afamin were observed between control and type 1 DM were (58.47 ± 8.13), and (63.07 ± 5.53) respectively. Our finding showed that increase serum afamin concentration in type 2 diabetes patients can be used as a biomarker for predicting diabetes mellitus.